2011
DOI: 10.4236/jwarp.2011.39076
|View full text |Cite
|
Sign up to set email alerts
|

On the Physical Composition of Solid Wastes in Selected Dumpsites of Ogbomosoland, South-Western Nigeria

Abstract: Solid wastes have varied compositions and constituents from place to place. The study area is not an excep- tion. The entire 5 Local Government Area (LGA)s of Ogbomosoland were surveyed and about 40 major dumpsites were identified across the spread. Twenty-five (25) of these were selected, five (5) each per LGA, for the study. The wastes were collected from the dumps, sorted, weighed and classified according to their constituents. The densities of wastes from the 25 dumpsites were also determined. The overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Municipal solid waste (MSW) also known as urban solid waste is defined as non-air and sewage emissions generated within and disposed by the municipality. These includes household waste, commercial refuse, construction and demolition debris, dead animals and abandoned vehicles [2]. MSW is mainly characterized by paper, vegetable matter, plastics, textiles, metals, rubber and glasses [3].…”
Section: Introductionmentioning
confidence: 99%
“…Municipal solid waste (MSW) also known as urban solid waste is defined as non-air and sewage emissions generated within and disposed by the municipality. These includes household waste, commercial refuse, construction and demolition debris, dead animals and abandoned vehicles [2]. MSW is mainly characterized by paper, vegetable matter, plastics, textiles, metals, rubber and glasses [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hazards posed by such waste dumpsite are not only in term of odor and presence of disease causing micro-organism, but can arise from the radiation emanating from such dumpsite (Ojoawo et al, 2011), which occur as results of accumulation and reaction of different radioactive materials in the waste indiscriminately dumped on open waste site. At waste dumpsites, there are possibilities for radiation to be emitted due to the presence of radioactive waste in the landfills as well as naturally occurring radionuclides in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…The values were 56% and 52% for the wet and dry season, respectively. The average composition of waste in Nigeria is approximately 50-70% putrescible and 30-50% non-putrescible [5,6], presenting much resource recovery potentials in composting and biogas renewable energy. Also, Olabode and Lawrence [26] mentioned that 53% of all goods, packaged in plastics, accounts for approximately 20% of total waste generated in the country.…”
Section: Overview Of Mswm and Wte Potentialsmentioning
confidence: 99%
“…This development is stirring curiosity on the level of waste management and its developmental process in low-income economies. Also, research has shown that the predominant MSW stream in many developing economies is the organic waste [5,6] and substantial energy can potentially be generated through technological processes from municipal waste.…”
Section: Introductionmentioning
confidence: 99%